Three-Dimensional Upper Body Kinematics and Inter-articular Kinematic Sequence During a Canoe Polo Throw - Assila, Najoua; Delavallade, Cyril; Blache, Yoann; Berger-Vachon, Christian; Collotte, Philippe; Duprey, Sonia (Frontiers in Sports and Active Living, 2021)
Canoe polo is an increasingly popular discipline requiring both kayaking and ball-handling skills. While the kinematics of the upper body during throw has been investigated for several overhead sports, the canoe polo throw has still to be studied. Therefore, the aim of this study is to analyze the canoe polo throw kinematics in terms of angles and inter-articular sequencing to understand its specificity. A secondary aim was to investigate whether adding pelvis mobility has an impact. Nineteen male players of canoe polo were equipped with reflective body markers for the throw analysis. They performed 5 throws with the pelvis fixed and 5 throws with additional pelvic mobility in rotation around a vertical axis. Inverse kinematics was performed with OpenSim providing pelvis, trunk, and glenohumeral rotations. Angular velocities were calculated to build the inter-articular sequences relative to these throws. Statistical parametric mapping was used to assess the effect of pelvis mobility on the throwing kinematics. Similar kinematics patterns as in other overhead sports were observed, however, a different inter-articular sequence was found for the canoe polo throw with a maximal angular velocity occurring sooner for the thorax in axial rotation than for the pelvis in rotation. While the limitation of rotation of the pelvis around a vertical axis has an influence on the pelvis and trunk kinematics, it did not modify the kinematic sequence.